Tribo-mechanical properties and biocompatibility of Ag-containing amorphous carbon films deposited onto Ti6Al4V - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Franke, Carlo; Kokalj, David; Stangier, Dominic; Filor, Viviane; Mateus-Vargas, Rafael Hernán; Oltmanns, Hilke; Kietzmann, Manfred; Meißner, Jessica; Hein, Maxwell; Pramanik, Sudipta; et al. (Surface and Coatings Technology)
The addition of Ag to amorphous carbon (a-C) films is highly effective in tailoring the tribo-mechanical properties and biocompatibility. For biomedical applications, Ag-containing a-C (a-C:Ag) represents a promising film material for improving the biofunctional surface properties of Ti-based alloys. In a sputtering process, a-C:Ag films, with Ag contents up to 7.5 at.%, were deposited with a chemically graded TixCy interlayer onto Ti6Al4V. The tribo-mechanical and biocompatible properties of a-C:Ag were evaluated. The influence of the Ag content on these properties was analyzed and compared to those of uncoated Ti6Al4V. Raman spectroscopy reveals that the amount of incorporated Ag does not induce significant structural changes in the disordered network, only a reduced number of vacancies and sp3-coordinated C bonds within the sp2-dominant a-C network is assigned to the films with high Ag concentration. With increasing Ag content, stresses, hardness, and elastic modulus decrease from (2.02 ± 0.07) to (1.15 ± 0.03) GPa, from (17.4 ± 1.5) to (13.4 ± 0.9) GPa, and from (171.8 ± 8.1) to (138.5 ± 5.8) GPa, respectively. In tribometer tests, the friction behavior against Al2O3 in lubricated condition with a simulated-body-fluid-based lubricant is not affected by the Ag concentration, but the Al2O3 counterpart wear is reduced for all a-C:Ag films compared to a-C. The friction against ultra-high-molecular-weight polyethylene (UHMWPE) decreases continuously with increasing Ag concentration and the counterpart wear is lower at higher Ag contents. Compared to a-C:Ag, Ti6Al4V demonstrates lower friction against UHMWPE and higher friction against Al2O3. The a-C:Ag films are not exposed to abrasion by Al2O3 or pronounced material transfer of UHMWPE. The hardness difference and chemical affinity between the friction partners are decisive for the tribological behavior of a-C:Ag. Compared to Ti6Al4V, the a-C:Ag films show antibacterial activity against Staphylococcus aureus, while the proliferation of osteoblast-like cells is reduced by Ag.

Intermetallic Phases Identification and Diffusion Simulation in Twin-Roll Cast Al-Fe Clad Sheet - Křivská, Barbora; Šlapáková, Michaela; Veselý, Jozef; Kihoulou, Martin; Fekete, Klaudia; Minárik, Peter; Králík, Rostislav; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Materials)
Aluminium steel clad materials have high potential for industrial applications. Their mechanical properties are governed by an intermetallic layer, which forms upon heat treatment at the Al-Fe interface. Transmission electron microscopy was employed to identify the phases present at the interface by selective area electron diffraction and energy dispersive spectroscopy. Three phases were identified: orthorhombic Al5Fe2, monoclinic Al13Fe4 and cubic Al19Fe4MnSi2. An effective interdiffusion coefficient dependent on concentration was determined according to the Boltzmann–Matano method. The highest value of the interdiffusion coefficient was reached at the composition of the intermetallic phases. Afterwards, the process of diffusion considering the evaluated interdiffusion coefficient was simulated using the finite element method. Results of the simulations revealed that growth of the intermetallic phases proceeds preferentially in the direction of aluminium.
Keywords: General Materials Science

Additively processed TiAl6Nb7 alloy for biomedical applications - Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Laser beam melting (LBM) is an advanced manufacturing technology providing special features and the possibility to produce complex and individual parts directly from a CAD model. TiAl6V4 is the most common used titanium alloy particularly in biomedical applications. TiAl6Nb7 shows promising improvements especially regarding biocompatible properties due to the substitution of the hazardous vanadium. This work focuses on the examination of laser beam melted TiAl6Nb7. For microstructural investigation scanning electron microscopy including energydispersive x-ray spectroscopy as well as electron backscatter diffraction are utilized. The laser beam melted related acicular microstructure as well as the corresponding mechanical properties, which are determined by hardness measurements and tensile tests, are investigated. The laser beam melted alloy meets, except of breaking elongation A, the mechanical demands like ultimate tensile strength Rm, yield strength Rp0.2, Vickers hardness HV of international standard ISO 5832-11. Next steps contain comparison between TiAl6Nb7 and TiAl6V4 in different conditions. Further investigations aim at improving mechanical properties of TiAl6Nb7 by heat treatments and assessment of their influence on the microstructure as well as examination regarding the corrosive behavior in human bodylike conditions.
Keywords: Laser beam melting; titanium alloy; TiAl6Nb7; biomedical engineering; implants

High Temperature Annealing of Twin-Roll Cast Al-Li-Based Alloy Studied by In-situ SEM and STEM - Cieslar, Miroslav; Králík, Rostislav; Bajtošová, Lucia; Křivská, Barbora; Hájek, Michal; Belejová, Sára; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Microscopy and Microanalysis)
Keywords: Instrumentation

Novel AgCa and AgCaLa alloys for Fe-based bioresorbable implants with adapted degradation - Krüger, Jan Tobias; Hoyer, Kay-Peter; Filor, Viviane; Pramanik, Sudipta; Kietzmann, Manfred; Meißner, Jessica; Schaper, Mirko (Journal of Alloys and Compounds)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Intermetallic Phase Growth in Al-steel Clad Strip during In-situ Heating in TEM - Křivská, Barbora; Šlapáková, Michaela; Minárik, Peter; Fekete, Klaudia; Králík, Rostislav; Stolbchenko, Mykhailo; Schaper, Mirko; Grydin, Olexandr (Microscopy and Microanalysis)
Keywords: Instrumentation

Investigating the microstructure of an additively manufactured FeCo alloy: an electron microscopy study - Pramanik, Sudipta; Tasche, Lennart; Hoyer, Kay-Peter; Schaper, Mirko (Additive Manufacturing)
Keywords: Industrial and Manufacturing Engineering; Engineering (miscellaneous); General Materials Science; Biomedical Engineering

Strength enhancement of AlMg sheet metal parts by rapid heating and subsequent cold die stamping of severely cold-rolled blanks - Camberg, Alan Adam; Andreiev, Anatolii; Pramanik, Sudipta; Hoyer, Kay-Peter; Tröster, Thomas; Schaper, Mirko (Materials Science and Engineering: A)

Correlation between Taylor Model Prediction and Transmission Electron Microscopy-Based Microstructural Investigations of Quasi-In Situ Tensile Deformation of Additively Manufactured FeCo Alloy - Pramanik, Sudipta; Tasche, Lennart; Hoyer, Kay-Peter; Schaper, Mirko (Journal of Materials Engineering and Performance)
Abstract Within this research, the multiscale microstructural evolution before and after the tensile test of a FeCo alloy is addressed. X-ray µ -computer tomography (CT), electron backscattered diffraction (EBSD), and transmission electron microscopy (TEM) are employed to determine the microstructure on different length scales. Microstructural evolution is studied by performing EBSD of the same area before and after the tensile test. As a result, $$\langle$$ ⟨ 001 $$\rangle$$ ⟩ ||TD, $$\langle$$ ⟨ 011 $$\rangle$$ ⟩ ||TD are hard orientations and $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ ||TD is soft orientations for deformation accommodation. It is not possible to predict the deformation of a single grain with the Taylor model. However, the Taylor model accurately predicts the orientation of all grains after deformation. {123} $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ is the most active slip system, and {112} $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ is the least active slip system. Both EBSD micrographs show grain subdivision after tensile testing. TEM images show the formation of dislocation cells. Correlative HRTEM images show unresolved lattice fringes at dislocation cell boundaries, whereas resolved lattice fringes are observed at dislocation cell interior. Since Schmid’s law is unable to predict the deformation behavior of grains, the boundary slip transmission accurately predicts the grain deformation behavior.

Correlation between pre- and post-treatments of additively manufactured 316L parts and the resulting low cycle fatigue behavior - Garthe, Kai-Uwe; Hoyer, Kay-Peter; Hagen, Leif; Tillmann, Wolfgang; Schaper, Mirko (Rapid Prototyping Journal)
Purpose The currently existing restrictions regarding the deployment of additively manufactured components because of poor surface roughness, porosity and residual stresses as well as their influence on the low-cycle fatigue (LCF) strength are addressed in this paper. Design/methodology/approach This study aims to evaluating the effect of different pre- and post-treatments on the LCF strength of additively manufactured 316L parts. Therefore, 316L specimens manufactured by laser powder bed fusion were examined in their as-built state as well as after grinding, or coating with regard to the surface roughness, residual stresses and LCF strength. To differentiate between topographical effects and residual stress-related phenomena, stress-relieved 316L specimens served as a reference throughout the investigations. To enable an alumina coating of the 316L components, atmospheric plasma spraying was used, and the near-surface residual stresses and the surface roughness are measured and investigated. Findings The results have shown that the applied pre- and post-treatments such as stress-relief heat treatment, grinding and alumina coating have each led to an increase in LCF strength of the 316L specimens. In contrast, the non-heat-treated specimens predominantly exhibited coating delamination. Originality/value To the best of the authors’ knowledge, this is the first study of the correlation between the LCF behavior of additively manufactured uncoated 316L specimens in comparison with additively manufactured 316L specimens with an alumina coating.